Intra-EU mobility of third-country nationals - State of play and prospects - Pascouau, Yves (Brussels, 2013)
"EU labour migration policy is a sensitive issue to deal with. It has been developed on a sectoral basis, i.e. through the adoption of directives targeting selective persons. Currently, any further development is made very difficult due to the economic crisis and the negative political climate in member states. Hence, the adoption of EU rules governing the admission of third-country nationals appears somehow impossible. However, and given the serious challenges that the EU and its member states will have to face, or are already facing, with respect to labour shortages, it is necessary to move forward. In this difficult context, one politically-acceptable opportunity remains: the development of intra-EU mobility facilities for migrant workers already residing in the member states. This Discussion Paper by Yves Pascouau aims to explore how intra-EU mobility could be improved at EU level. It analyses existing EU rules and concludes that the right to freedom of movement is awarded to limited categories of third-country nationals and under different regimes which do not make mobility attractive. Given the inadequacy of such a situation, the paper proposes solutions to enhance intra-EU mobility for migrant workers who already reside in the EU."